Estudos arqueométricos de solos de terra preta de índio (TPI) e a modificação antropogênica no Oriente Amazônico - HOSN, Majd Nidal Aboul (Universidade Federal do Oeste do Pará, 2023)
The eastern Amazon region is characterized by the presence of anthropogenic soils where formation occurs by the human activity of indigenous community for a long period of time. The populations established in the eastern portion of the Amazon migrated from different areas creating a multicultural environment with different technologies for the production of tools, artifacts and ecofacts, diversifying their lithic and ceramic industries that helped daily life and are evidenced in the archaeological remains. Soils known as Terra Preta de Índio (TPI) are formed by daily activities and are composed of high levels of macro and micronutrients, coal, organic matter, archaeological ceramics and lithic material. The chemical and mineral properties of TPI soils from the Bitoca I and Bitoca II sites (eastern region of the Amazon), generated new soil data from archaeological sites in the eastern Amazon, tested interdisciplinary with modern archaeometric techniques such as X-ray diffractometry ( XRD), Fourier Transform Infrared Spectroscopy (FTIR), Scanning Electron Microscopy (SEM), and traditional techniques of total chemical and fertility and nutrient analysis for CTC, SB, pH. Result demonstrates the daily life inside the village, possible evidence of residence, bonfires, among other archaeological structures, and the identification of features such as bowl sediment and ceramic sediment with soil in probable food contexts. Analyzes show minerals (kaolinite, quartz, anatase, hematite, goethite and gibbsite), high levels of macro and micronutrients and the presence of cauxi and cariapé, correlated with the literature for TPI soils in the region. Through dating, we can see a chronology of indigenous populations for a millenary period of continuous occupation, a factor that certainly contributed to the pedogenetic process of formation of the TPI and the maintenance and enrichment of the ecosystem and local biodiversity, evidencing the importance of these soils, for the environment and its populations.